Cover Image, Volume 88, Issue 6. Issue 6 (14th May 2020) - Panda, Alok Kumar; Chakraborty, Ayon; Nandi, Sandip Kumar; Biswas, Ashis
Abstract : Obverse Cover: The cover image is based on the Original Article The impact of different mutations at arginine141 on the structure, subunit exchange dynamics and chaperone activity of Hsp16.3 by Ashis Biswas et al., https://doi.org/10.1002/prot.25864 .